Política nacional de resíduos sólidos: uma análise da gestão em municípios de pequeno porte - Luiz, Gustavo de Carvalho (2018)
This dissertation presents a multi-case study that was applied to small municipalities that have outstanding actions in the field of solid waste management. By this, it is sought to verify the best solid waste management practices of performed in small municipalities, considering that such public policies are important from a sustainability perspective. The general objective of the research was to propose the best solid waste management practices for small municipalities, in the light of the National Solid Waste Policy (PNRS). About the specific objectives, we sought to map the actions foreseen in the PNRS that are executed in the surveyed cities, as well as the actions that are pending implementation. Also were presented statistical data on solid waste management in the national context. The dissertation is supported by Law n. 12.305/2010, which instituted the National Policy on Solid Waste. Through this higher legislation, the federal government has established a series of guidelines for states and municipalities to qualify waste management and promote sustainable actions. From this perspective, the paper presented the following research problem: What are the good solid waste management practices implemented by municipalities that have a population of up to 50 thousand inhabitants? The methodology used involved an exploratory study, with a qualitative and prescriptive approach. To achieve the results, consultations were carried out on theoretical references related to the subject, as well as on official data and research institutes. In order to verify the alignment of the theoretical statements with the management practices, the research was complemented with a multiple case study, made from interviews with authorities from five municipalities of up to 50.000 inhabitants, and that have outstanding actions in the field of management of solid waste. For each region of the country, one municipality was selected. Considering the factors that were analyzed and the results verified, it was verified that some municipalities have a close alignment to the precepts of the PNRS, serving as reference to other municipalities. On the other hand, there are municipalities that are still in the process of adapting to Law 12.305/2010, having performed some specific actions, but with other actions, considered mandatory, still pending of implementation. The study's general objective was reached with the construction of the final research product, in the form of a pamphlet about good solid waste management practices to be carried out by small municipalities. The objective of the pamphlet is to help the correct direction of the public policies focused on the theme. Also, it seeks to encourage more discussions and reflections, aiming at responsible and sustainable solid waste management for all populations.